PENGETAHUAN SADARI MELALUI PENDIDIKAN KESEHATAN MEDIA POSTER DAN METODE DEMONSTRASI - Halim, Aisyah Nabilah; Purwanti, Yanik; Azizah, Nurul (Jurnal Ilmiah Kebidanan Imelda, 2023)
In Indonesia, one of the most common causes of death is breast cancer. Breast cancer is a normal thing to happen to women. The danger of breast cancer can be reduced and can be recognized early so as not to cause malignancy. The use of breast self-examination (BSE) is a strategy to prevent breast cancer at an early stage. The purpose of this study was to determine the effect of health education through poster media and demonstration methods on the knowledge of SMA Al-Fattah Buduran Sidoarjo students about BSE. This research method uses the Quasi Experiment with the Two Group Pretest and Posttest design and uses the Mann-Whitney statistical test. All participants in this study were female high school students at Al-Fattah Buduran Sidoarjo. The research sample consisted of 80 female students who were divided into two groups of 40 each: the poster media group and the demonstration method group. The results of this research are the poster media with a p-value of 0.000, the demonstration method with a p-value of 0.000, and the difference between poster media and demonstration methods with a p-value of 0.054. From the results of the combined poster media with the demonstration method there is no significant difference.